Rodgers & Hammerstein's Oklahoma! [videorecording (DVD)] - Jackman, Hugh; Gabrielle, Josefina; Hensley, Shuler; Polycarpou, Peter; Johnston, Jimmy (Actor); Simon, Vicki; Lipman, Maureen; Rodgers, Richard, 1902-1979; Hammerstein, Oscar, II, 1895-1960; Riggs, Lynn, 1899-1954; Rodgers, Richard, 1902-1979 (Samuel Goldwyn Films, 2023)
Cowboy Curly McClain tries to win the heart of a girl in a singing and dancing extravaganza. The Royal National Theatre's Olivier Award-winning 1998 production of Rodgers & Hammerstein's Oklahoma! starring Hugh Jackman as Curly. This Rodgers & Hammerstein classic is an exuberant and tuneful musical full of cowboys, farmers, romance and fearless optimism.